Repair of a Chronic Triceps Tendon Rupture in a Dog Using an Autogenous Thoracolumbar Fascia Onlay Graft - Wood, Christopher J.; Cashmore, Ricky G. (VCOT Open, 2021)
A 5-year-old 38 kg entire male German Shepherd dog was referred for persistent non-weight bearing left thoracic limb lameness 5 weeks following failed triceps tendon repair. Physical exam revealed complete incompetence of the triceps mechanism with a large palpable defect proximal to the olecranon and when the shoulder was fixed in extension, the elbow could be fully flexed. A purulent draining tract was present on the caudolateral aspect of the distal brachium. Staged tendon repair was delayed until resolution of infection to allow for improved healing. Culture following surgical exploration of the traumatized area with resection of sinus tract and interposed fibro-granulomatous tissue yielded no growth. Definitive triceps brachii tendon repair was augmented with an autogenous thoracolumbar fascia onlay graft. Postoperatively, the repair was protected with a spica splint and the left thoracic limb immobilized with the elbow maintained in an extended position for 6 weeks. Re-evaluation 7 months later revealed the patient to be free of lameness. Disruption of the triceps brachii tendon is a rarely reported tendon injury with chronic disruption of triceps tendon associated with a guarded prognosis. To the authors knowledge, successful surgical repair of tendinous injury incorporating the use of an autogenous thoracolumbar fascia onlay graft has not previously been described.
Keywords: tendon repair; tendon injury; lameness; dogs